Anxiety and Depressive Symptoms During Pregnancy, Perceived Control and Posttraumatic Stress Symptoms After Childbirth: A Review Article - Laila Hassan Bukhade et al. (International Journal of Scientific Research and Innovative Studies, 2025)
Psychological birth trauma and childbirth-related posttraumatic stress disorder (CB-PTSD) affect a substantial number of mothers worldwide annually, representing a significant burden of disease. This review synthesizes current evidence on the relationships between antenatal anxiety and depressive symptoms, perceived control during childbirth, and postpartum posttraumatic stress symptoms. A growing body of longitudinal research indicates that antenatal mood disorders serve as significant risk factors for CB-PTSD, with perceived control during labor and delivery functioning as a key mediating and moderating variable. Evidence from systematic reviews demonstrates that brief trauma-focused psychological therapies delivered in the early postpartum period show moderate to large effects in reducing CB-PTSD symptoms. Furthermore, multi-component antenatal interventions, including cognitive behavioral therapy and psychoeducation, may be effective in preventing psychological birth trauma, particularly among women with histories of traumatic life events. This review examines the prevalence, risk factors, and underlying mechanisms linking antenatal psychological distress to postpartum traumatic stress, with particular emphasis on the protective role of perceived control. Clinical implications and recommendations for screening and intervention are discussed. Keywords: childbirth-related posttraumatic stress disorder, antenatal anxiety, perinatal depression, perceived control, traumatic birth, prevention Received Date: February 25, 2025 Accepted Date: March 18, 2025 Published Date: April 01, 2025 Available Online at : https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/632